ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL PEMECAHAN MASALAH MATEMATIKA MATERI TRIGONOMETRI - Viktorino Pires; Farida Daniel; Prida N. L. Taneo (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2022)
Mathematics problem-solving is a process to apply te previous knowledge into a new situation. The purpose of this study is to investigate the students’ errors to finish mathematics problem-solving exercises. The subject of the study were 15 students of Xa grade of  SMAK Stella Maris Niki-Niki. The researcher used a qualitative description as the method and collected the data through observation, test, and interview. In analyzing the data, the researcher adopted a model from Miles and Huberman with a validity test through the triangulation technique. The result of this study showed that the student’s errors in problem-solving mathematics in the form of error concept, principle, technical and algorithm/procedure. In general, the factors cause students error were low ability to understand the concept, students did not accurate and they were unfamiliar to finish mathematics problem-solving exercises.